Relationship Between Student Perceptions of Teacher Creativity with Student Learning Achievement in Tangerang - Zubairi, Zubairi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study aims to determine student perceptions of teacher creativity in managing class (X). Student achievement of Islamic religious education in Cipondoh District, Tangerang City (Y). Whether or not there is a relationship between students' perceptions of teacher creativity in managing classes and student achievement in Islamic religious education at State Junior High Schools in Cipondoh District, Tangerang City. This study uses a quantitative approach. The research subjects totaled 32 respondents, using a stratified random sampling technique. Data collection uses a questionnaire instrument (X) and a report card value documentation instrument to collect data (Y). The collected research data were analyzed using descriptive statistical analysis techniques. Testing the hypothesis shows a positive relationship between student perceptions of teacher creativity in managing classes and student achievement in Islamic religious education at Cipondoh District Public Middle School, Tangerang City. This can be seen from the recount (observation ratio value) of 0.641, greater than the rtable (correlation table value) at the significance level of 5%:0.349 and 1%:0.449. This shows that the teacher's creativity determines 64% of the variation in Islamic religious education learning achievement scores. From the results of this study, it was concluded that there was a positive relationship between students' perceptions of teacher creativity in managing classes and student achievement in Islamic religious education, in the sense that the higher student perceptions of teacher creativity in managing classes, the better student achievement in religious education.